Tracking temporal response dynamics in the ventral striatum during social feedback in anorexia nervosa: A functional magnetic resonance imaging exploratory study. Issue 10 (6th September 2021) - Membrives, Sonia; López‐Solà, Marina; Fernández‐Aranda, Fernando; Sánchez, Isabel; Martínez‐Zalacaín, Ignacio; Palao, Diego; Pujol, Jesus; Menchón, Jose M.; Davey, Chris G.; Harrison, Ben J.; Keating, Charlotte; Rossell, Susan L.; et al.
Abstract: Objective: Research suggests abnormalities in reward‐based processes in anorexia nervosa (AN). However, few studies have explored if such alterations might be associated with different temporal activation patterns. This study aims to characterize alterations in time‐dependent processes in the ventral striatum (VS) during social feedback in AN using functional magnetic resonance imaging (fMRI). Method: Twenty women with restrictive‐subtype AN and 20 age‐matched healthy controls (HC) underwent a social judgment experimental fMRI task. Temporal VS hemodynamic responses were extracted in SPM for each participant and each social condition (acceptance/rejection). Results: Compared with age‐matched HC, patients with AN showed a significant time by group interaction of peak VS response throughout the task, with a progressive blunting of peak activation responses, accompanied by a progressive increase in baseline activity levels over time. Discussion: The results suggest an attenuated response pattern to repetitive social rejection in the VS in patients with AN, together with a difficulty in returning to baseline. The information obtained from this study will guide future, design‐specific studies to further explore alterations temporal dynamics. Abstract :